THE HIJIRI CALENDAR AND ITS CONFORMANCE WITH THE GREGORAIN CALENDAR BY MATHEMATICAL CALCULATIONS: 31st May 2022; 07th February 2023; 16th February 2023; 17th February 2023 - Abuelyamen, Salih Hamza (MATTER: International Journal of Science and Technology, 2023)
The objective of this research is to develop a mathematical procedure to construct a Hijri calendar that is consistent with the Gregorian calendar. Our hypothesis was derived from the Quran Chapter, Alkahf verse (25), which states “They remained in their cave for three hundred years, adding nine”. We understand this verse to mean “every 300 solar years equivalent exactly to 309 lunar years”. The starting point was to locate the number of days for each month of each Hijri year. We found that the distribution of number of days per month coincided in the two rounds of the 309 Hijri years. Accordingly, we prepared a list of number of days per month for 1545 Hijri years. Hence, we constructed Hijri calendar starting consecutively from 1 Muharram 1AH to any Hijri Date. We considered the Gregorian Date consistent with the first of Ramadan 1442AH as a relevant reference versus the historical reference of the migration of Prophet Mohammed صلى الله عليه وسلم to Medina. Finally, we compared our results with previous official dates Therefore any Gregorian date corresponds to Hijri date could be known.